Severe vertebral artery stenosis treated by directional atherectomy - Yongquan Gu; Jianming Guo; Lianrui Guo; Shijun Cui; Hanaa-Dakour Aridi; Mahmoud B Malas; Zhu Tong; Yixia Qi; Lixing Qi (Vascular Investigation and Therapy, 2018)
We report the outcomes of directional atherectomy using a distal protective device and drug-coated balloon angioplasty in four patients with severe atherosclerotic vertebral artery stenosis. All cases were clinically successful with complete resolution of the symptoms. Immediate and postoperative results showed a good technical success. These results suggest that vertebral artery stenosis treated with directional atherectomy is technically feasible and may be a safe and effective option when performed by experienced endovascular surgeons.